A Rare Presentation of Primary Plasma Cell Leukemia: A Case Report and Review of Literature - Gaurav T, Damdar; Anusree, Prabhakaran (Asian Pacific Journal of Cancer Biology, 2022)
Background: The primary plasma cell leukemia (pPCL) is an aggressive plasma cell neoplasm. It is diagnosed by the presence of an absolute plasma cell count of >2 × 109/L or 20% plasma cells in the peripheral blood. pPCL is rare and reported to be <1 in a million. Hence, our case report is a rare opportunity to describe clinical presentation and management of pPCL. Case Details: A 72-year-old male patient with benign prostatic hyperplasia, presented to the hospital for cough, breathlessness, and intermittent fever of one month. On arrival, he was tachypnoeic with altered sensorium and rales in his chest. Laboratory examination showed anemia, leucocytosis, and thrombocytopenia. The peripheral blood smears revealed 25-30% circulating atypical plasmacytoid cells. Flow cytometry on the peripheral blood revealed 58.7% lymphoid cells. Out of the total lymphoid cells, 73.6 % cells were characterized by expression of CD38, CD138, CD19, CD49d, CD43, CD27, CD81 (96.9% dim positives) CD 56 with dim kappa light chain restriction suggestive of PCL. Furthermore, serum protein electrophoresis and serum immunofixation showed an M-band (0.53g) of IgG kappa subtype. However, the patient developed lower respiratory tract infections with multi-organ dysfunction and he succumbed to the same. Conclusion: The prognosis of pPCL is very poor and the high risk of infective complications. Early diagnosis and optimal chemotherapy would be the key to the management. Detailed peripheral blood film examination and characterization of abnormal cells with immune phenotyping are of utmost importance in diagnosing pPCL.